SOME ISSUES OF RATIONAL AND EFFECTIVE USE OF ECOTOURISM RESOURCES (on the example of Dekhanabad district) (Scientific journal of the Fergana State University, 2024)
The article examines some aspects of the development of mountain and pre-mountain ecotourism in Dehkhanabad district, especially the natural and territorial conditions, and how pre-mountain ecotourism is directly related to the interaction between nature and man. There are many natural attractions in the Kashkadarya Basin, which directly serves as a place for tourists to relax and recuperate. In this regard, it was informed that the mountains and mountainous areas in the mountainous region are a reserve that is not open to local and foreign tourists and some aspects of ecotourism.